Az új vállalkozások gazdaságra gyakorolt hatásainak vizsgálata nemzetközi összehasonlitásban - Zoltán J. Ács; László Szerb; Attila Varga; Jozsef Ulbert; Eva Bodor (Max Planck Institute for Research into Economic Systems, 2004)
– The analysis of the effect of new ventures on the economy has been widely investigated over the last decade. However, the Global Entrepreneurship Monitor (GEM) international research was the first that provided a consistent and comparable estimation of the entrepreneurial activity over nations. The present study describes the most important result of the GEM research over the 2001-2003 time period with focusing on Hungary. Using the two most important rates, the Total Entrepreneurial Activity (TEA) index and the Firm Entrepreneurial Index (FEI), Hungary can be found in the middle range of the participating countries. Our situation is better in terms of regional comparison in the Central Eastern European region - Croatia, Poland, Russia and Slovenia -, and slightly better comparing to the European Union average. Since the new firm formation effect on economic growth and employment creation outweigh that of the existing companies by five to six times, Hungarian entrepreneurship policy should focus more on supporting the newly created enterprises
Keywords: 330; Unternehmer; Unternehmensgründung; Vergleich; Ungarn; Welt